Study on Axial Compression Stability of Q345 Large-Section Angle Steel Columns - Haoyuan Chen; Hao Chen; Ke Cao; Yaojie Guo (Buildings, 2023)
With the growing demand for the bearing capacity of columns, large-section angle steel (LAS) columns have been widely adopted. Q345 is the most commonly used steel, but research on the axial compression stability of LAS columns mainly focuses on steels with 420 MPa and above. In order to study the buckling behavior of Q345 LAS columns, a total of 96 specimens are subjected to axial compression tests. The test results are compared with the specification and analyzed. Based on test data, an accurate finite element model of the Q345 LAS column is established, and the parametric analysis is carried out through the model. The results show that the buckling mode of Q345 LAS columns is flexural buckling, and local buckling is not observed. The axial compression stability coefficient of Q345 LAS short columns is significantly higher than the result of the specification. The reasons come from the constitutive model and the buckling mode, and the influence of section size can be ignored. The curve a in GB50017-2017 and Eurocode 3 can be used to calculate the axial compression stability of Q345 LAS columns. Finally, a new column curve is proposed to calculate the axial compression stability of Q345 LAS columns.